NAD deficiency, congenital malformations and niacin supplementation - Shi, H; Enriquez, A; Rapadas, M; Martin, E; Wang, R; Moreau, J; Lim, C; Szot, J; Ip, E; Hughes, J; Sugimoto, K; Humphreys, D; et al. (Massachusetts Medical Society, 2017)
Background Congenital malformations can manifest as combinations of phenotypes that co-occur more often than expected by chance. In many such cases it has proved difficult to identify a genetic cause. We sought the genetic cause of cardiac, vertebral and renal defects, amongst others, in four unrelated patients. Methods Genomic sequencing was used to identify potentially pathogenic gene variants in four families. The variants were functionally tested using in vitro enzyme activity assays, and by quantifying metabolites in patient plasma. We engineered mouse models with similar variants using CRISPR/Cas9. Results Variants were identified in 3-hydroxyanthranilic acid 3,4-dioxygenase (HAAO) and kynureninase (KYNU) genes encoding kynurenine pathway enzymes. Three patients carried homozygous variants predicting loss-of-function changes in the HAAO or KYNY proteins (HAAO p.D162*, HAAO p.W186*, or KYNU p.V57Efs*21). Another patient carried heterozygous KYNU variants (p.Y156* and p.F349Kfs*4). The mutant enzymes had greatly reduced activity in vitro. Nicotinamide adenine dinucleotide (NAD) is synthesized de novo from tryptophan via the kynurenine pathway. The patients had reduced circulating NAD levels. Haao or Kynu null mouse embryos developed similar defects to the patients due to NAD deficiency. In null mice, averting NAD deficiency during gestation prevented defects. Conclusions Disruption of NAD synthesis causes a deficiency and congenital malformations in humans and mice. Niacin supplementation during gestation prevented the malformations in mice.